Black Nb2O5 nanorods with improved solar absorption and enhanced photocatalytic activity. Issue 9 (1st February 2016) - Zhao, Wenli; Zhao, Wei; Zhu, Guilian; Lin, Tianquan; Xu, Fangfang; Huang, Fuqiang
Abstract : Black Nb2 O5 nanorods with an active exposed (001) surface were firstly prepared. Substantial Nb 4+ and oxygen vacancies were introduced into black Nb2 O5, resulting in the enhanced absorption in solar absorption. The advantage of black Nb2 O5 was also proved by its more efficient PEC performance and higher photocatalytic H2 generation activity than pristine Nb2 O5 . Abstract : Black titania, with greatly improved solar absorption, has demonstrated its effectiveness in photocatalysis and photoelectrochemical cells (PEC), inspiring us to explore the blackening of other wide band-gap oxide materials for enhanced performance. Herein, we report the fabrication of black, reduced Nb2 O5 nanorods (r-Nb2 O5 ), with active exposed (001) surfaces, and their enhanced photocatalytic and PEC properties. Black r-Nb2 O5 nanorods were obtained via reduction of pristine Nb2 O5 by molten aluminum in a two-zone furnace. Unlike the black titania, r-Nb2 O5 nanorods are well-crystallized, without a core–shell structure, which makes them outstanding in photocatalytic stability. Substantial Nb 4+ cation and oxygen vacancies (VO ) were introduced into r-Nb2 O5, resulting in the enhanced absorption in both the visible and near-infrared regions and improved charge separation and transport capability. The advantage of the r-Nb2 O5 was also proved by its more efficient photoelectrochemical performance (138 times at 1.23 VRHE ) and higher photocatalytic hydrogen-generation activity (13 times) than pristine Nb2 O5 . These results indicate that black r-Nb2 O5 is a promising material for PEC application and photocatalysis.